Burdensomeness, Belongingness, and Capability: Assessing the Interpersonal–Psychological Theory of Suicide With MMPI-2-RF Scales. (June 2018) - Anestis, Joye C.; Finn, Jacob A.; Gottfried, Emily D.; Hames, Jennifer L.; Bodell, Lindsay P.; Hagan, Christopher R.; Arnau, Randolph C.; Anestis, Michael D.; Arbisi, Paul A.; Joiner, Thomas E.
Given the emerging body of literature demonstrating the validity of the interpersonal–psychological theory of suicide (IPTS), and the importance of increasing our understanding of the development of risk factors associated with suicidal behavior, it seems worthwhile both to expand IPTS research via Minnesota Multiphasic Personality Inventory–2–Restructured Form (MMPI-2-RF) correlates and to expand the availability of methods by which to assess the constructs of the IPTS. The present study attempted to do so in a large adult outpatient mental health sample by (a) inspecting associations between the IPTS constructs and the substantive scales of the MMPI-2-RF and (b) exploring the utility of MMPI-2-RF scale–based algorithms of the IPTS constructs. Correlates between the IPTS constructs and the MMPI-2-RF scales scores largely followed a pattern consistent with theory-based predictions, and we provide preliminary evidence that the IPTS constructs can be reasonably approximated using theoretically based MMPI-2-RF substantive scales. Implications of these findings are discussed.